If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x * 2x = 96 Reorder the terms for easier multiplication: 3 * 2x * x = 96 Multiply 3 * 2 6x * x = 96 Multiply x * x 6x2 = 96 Solving 6x2 = 96 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '6'. x2 = 16 Simplifying x2 = 16 Take the square root of each side: x = {-4, 4}
| 100=20t-3t^2 | | (9-w)(3w+1)=0 | | 16w-80=0 | | 12q^2-11qw-15w^2=0 | | A-4b=-24 | | 9x+15=x-1 | | 2(x+5)=2x-3 | | -33t^4+19t^3+2t^2=0 | | 3a-4b=56 | | 3a(a+2b)= | | 2x+11=2(x-5) | | 112w^3+34w^2-6w=0 | | 3x+4y=161 | | 3x+4y=171 | | 16x-96=-4x+-176 | | 10*lnx=0 | | 3y^2+12y-5y-20=0 | | y=2*ln(5*x) | | 3x-10=5x+22 | | 3y^2+18y-2y-12=0 | | 2r^2-7r-14r+49=0 | | 1=4x^2-16x-4 | | y^2+y-2y-2=0 | | 16x-16=-4x+-56 | | 21s+20+4s^2=0 | | -8x+64=4x+16 | | -2(4z-3)=14 | | -8x-64=4x+16 | | 9x^2+9y^2+12x-6y+4=0 | | 15y^2+59y-4=0 | | 6-13u+6u^2=0 | | 2s^3+7s^2+5s=0 |